PENERAPAN PROGRAM SINERGI PEMBERDAYAAN EKONOMI KOMUNITAS (PROSPEK) LEMBAGA POS KEADILAN PEDULI UMAT ( P K P U ) DALAM KEHIDUPAN SOSIAL EKONOMI KELOMPOK AMANAH KECAMATAN MEDAN AMPLAS - Alimul Hadi (Welfare StatE, 2013)
This study , entitled " Implementation of Community Economic Empowerment Synergy (PROSPECT) Pos Institute of Justice Care (PKPU) in the Socio-Economic Life Amanah Group Medan District Sandpaper " . This study aims to determine how the Application Program Community Economic Empowerment Synergy (PROSPECT) Pos Institute of Justice Care (PKPU) in the Socio-Economic Life Amanah Group Medan District Sandpaper . The results of this study are expected to be a reference source for the theory of the author, reader , and especially for the Institute as a reference to the model of policy development and implementation in the empowerment of SHG groups. The study was conducted at the Self-Help Groups (SHGs) Amanah districts Sandpaper Patronage PKPU field . This research is a descriptive study , in which all members of the group Amanah PROSPECT program as many as 10 people , the data retrieved . Data collection techniques to the study of literature and field studies . Empowerment program in terms of the provision of venture capital , skills and talents training , and mentoring routine . The data obtained were then analyzed and compiled in the form of a single table after it is explained qualitatively. Results of research conducted showed that the application of community economic empowerment program synergies (PROSPECT) , it can be concluded that the provision of such programs is less effort to meet the needs , but assistance in accordance with the standard of service runs made ​​by PKPU and greatly contribute to the improvement of socio-economic conditions of its members . Party organizations should pay more attention PKPU deficiencies in the services provided to members and better development of the field of the other services that the goal can be achieved optimally PKPU . Keywords : Social and Economic Prospects Program